So language. Very prescribe. Wow. - Glackin, Shane Nicholas (Sofia, 2019)
The philosophical dispute about linguistic normativity is one battlefield in a larger war over the nature of language as an object of scientific study. For those influenced by Wittgenstein, language involves following — or failing to follow — public, prescriptive rules; for Chomsky and his followers, language is a property of individual minds and brains, and the grammatical judgements of any mature individual speaker — her competence — cannot be, in any linguistic sense, “wrong”. As I argue here, the recent “doge meme” internet fad provides surprising evidence for the prescriptivist view. Normative attitudes towards linguistic practices are a ubiquitous feature of those practices, and there is no principled basis on which to regard them as non-linguistic.